Applying the Urban Political Ecology (UPE) Framework to Re-Visit Disaster and Climate Change Vulnerability-Risk Assessments - M. Bobby Rahman; Isye Susana Nurhasanah; Erwin Nugraha; Tetty Harahap (The Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
Abstract. Vulnerability and risk assessment (VRA) is increasingly becoming more popular as a tool to assess and evaluate the likelihood and externalities that are faced by urban areas because of environmental hazards and climate change. However, urban dynamics are increasingly putting communities in a vulnerable/riskier situation, calling for a more comprehensive and inter-disciplinary approach. Urban Political Ecology (UPE) was utilized as a framework to reflect upon the empirical findings and literature review with two urban villages (kelurahan) in Bandar Lampung, Indonesia